Execution of Security Rights in Islamic Banking at the Religious Court of Purbalingga - Triana, Nita (International Conference of Moslem Society, 2018)
This article examines the execution of a security interest in Islamic banking in the Islamic economic disputes in the Purbalingga Religious Court. The case of non-performing loans in the world of Islamic banking is often the case, this was due to the debtor defaults. Mortgages used as collateral can be executed based on the decision of the Religious Court. The method used in this research is a kind of field research with the approach of Socio Legal Research, including in the realm of non-doctrinal study. The results show the execution of a security interest in dispute sharia economy in Purbalingga Religious Court has been run in accordance with the mandate of the Act: On the substance of the Implementation of the decision of execution is the end of a case that is the result of what is required by the plaintiff are determined in a court of Religion with using the guidelines do not separate from the disciplinary proceedings contained in HIR or Rbg. On the Structure of Purbalingga Religious Court carry out executions by institutions that are available from the start to the filing of the petition to the Chairman of the Religious Courts, judges who will examine the final verdict, Executor who will call and will execute and when the auction Clerk role of the mentor State Property Office and Auction (KPKNL). Culturally law. Purbalingga Religious Court carry out the execution-based approaches to religion and culture. This approach proved to facilitate execution. Obstacles that faced in general, form, creditors often receive a guaranteed land and buildings where the land certificate is no longer appropriate to the actual situation, the Debtor is not willing to leave the place right dependents, barriers to the sale of objects auction execution which does not go unsold objects auction / auction. Constraints that normally occurs in the execution of this economic security rights dispute, can be resolved by various reinforcement structures / institutions and culture through the law chosen by the Purbalingga Religious Courts.